ANALISIS KEMAMPUAN PEDAGOGICAL CONTENT KNOWLEDGE MAHASISWA CALON GURU KIMIA MA/SMA - Evi Sapinatul Bahriah (EduChemia (Jurnal Kimia dan Pendidikan), 2017)
Abstract: This study aims to determine the ability of Pedagogical Content Knowledge (PCK) pre-service education of chemistry in MA/SMA. The method used is descriptive qualitative. The subjects consist of 30 students from the Department of Chemistry Education 8th semester of the academic year 2015/2016 FITK UIN Syarif Hidayatullah Jakarta in March to September 2016. The ability of PCK measured consists of seven components: knowledge of science, knowledge of goals, knowledge of students, knowledge of curriculum organization, knowledge of teaching, knowledge of assessment, and knowledge of resources. The instrument used in this study consisted of objective tests and oral tests. Data were analyzed with descriptive qualitative. The results of this study show that: 1) The percentage of the average value of the ability of PCK overall is 56.67% is included enough category. 2) The percentage of the average value of the ability of PCK highest is indicators Knowledge of science, KoSc amounted to 65.67% (good categories), while the percentage of the average value of the ability of PCK lowest is an indicator knowledge of students 26.67% (less than one category). 3) The ability of PCK pre-service education of chemistry is enough category. Abstrak: Penelitian ini bertujuan untuk mengetahui kemampuan Pedagogical Content Knowledge (PCK) calon guru kimia MA/SMA. Metode penelitian yang digunakan adalah metode deskriptif kualitatif. Subjek penelitian ini adalah 30 orang mahasiswa Jurusan Pendidikan Kimia semester 8 tahun akademik 2015/2016 FITK UIN Syarif hidayatullah Jakarta pada bulan Maret-September 2016. Kemampuan PCK yang diukur terdiri dari 7 komponen yaitu knowledge of science, knowledge of goals, knowledge of students, knowledge of curriculum organization, knowledge of teaching, knowledge of assessment, and knowledge of resources. Instrumen yang digunakan dalam penelitian ini terdiri dari tes objektif dan tes lisan. Data yang diperoleh dianalisis dengan teknik deskriptif kualitatif. Hasil penelitian ini menunjukkan bahwa: 1) Persentase nilai rata-rata kemampuan PCK calon guru kimia secara keseluruhan adalah sebesar 56,67% yang termasuk dalam kategori cukup. 2) Persentase nilai rata-rata kemampuan PCK calon guru kimia tertinggi adalah indikator pengetahuan terhadap konten sains (Knowledge of science, KoSc) sebesar 65,67% (kategori baik), sedangkan persentase nilai rata-rata kemampuan PCK calon guru kimia terendah adalah indikator pengetahuan terhadap karakteristik siswa (Knowledge of students, KoSt) sebesar 26,67% (kategori kurang sekali). 3) Kemampuan PCK calon guru kimia secara umum termasuk kategori cukup.